Improving Science Literacy using Basic Science Booklet for Indonesian Elementary Learners in Sanggar Belajar Penang, Malaysia - Yuliani Yuliani; Raharjo Raharjo; Endang Susantini; Widowati Budjiastuti; Sifak Indana; Firas Khaleyla (Universitas Muhammadiyah Malang, 2025)
Effectiveness of Basic Science Material Booklet to Improve Science Literacy for Indonesian Students in Malaysian Learning Studio. Science literacy is a skill necessary in the 21st century. However, at Sanggar Belajar managed by the Indonesian Community Organization (PERMAI) in Penang, Malaysia, teaching to train science literacy for elementary school students is still limited in terms of media and learning models. Therefore, this community service held on August 3rd 2024 was aimed to improve science literacy by of elementary learners at Sanggar Belajar Permai, Penang, Malaysia by enriching science materials using basic science booklets developed. The methods used was pre-implementation to develop booklet and test instrument, implementation of booklet, and evaluation. The learning outcome and science literacy skills was evaluated based on knowledge test. The results showed an increase in the learning outcome elementary school students at Sanggar Belajar Permai after learning using basic science booklets. Science literacy skills showed effective or very affective categories in almost all indicator. This indicates that the community service has been effective